Analisis Dimensions dengan Keyword Tafsir Ayat Ibadah menggunakan Teknik Bibliometrik - Fadia Luthfi Riyani (Gunung Djati Conference Series, 2023)
This study describes the development of the interpretation of the verses of worship in a comprehensive manner, by including the data that has been researched by the author along with the explanations. Searches with the keywords interpretation of religious verses are carried out on dimensions.ai using a quantitative method. The results of this research search present the findings of exploratory research on the interpretation of religious verses, as reflected in the research that has been described. In this study, the most research categories were Philosophy and Religious Studies. The development per year of the keyword interpretation of religious verses has increased in 2020. The author who plays an active role in scientific publications regarding the interpretation of religious verses is Muhammad Alfatih Suryadilaga. The most prolific place of publication is Mutawatir.